2023
DOI: 10.1002/adhm.202300556
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Recent Clinical Assessment of Commercial Chronic Wound Care Products

Abstract: Impaired wound healing after trauma, disorders, and surgeries impact millions of people globally every year. Dysregulation in orchestrated healing mechanisms and underlying medical complications make chronic wound management extremely challenging. Besides standard‐of‐care treatments including broad spectrum antibiotics and wound‐debridement, novel adjuvant therapies are clinically tested and commercialized. These include topical agents, skin substitutes, growth factor delivery, and stem cell therapies. With a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 161 publications
(192 reference statements)
0
6
0
Order By: Relevance
“…The RT-PCR observation (Figure C) was consistent with the amounts of the aforementioned pro- and anti-inflammatory cytokines assessed by ELISA (Figure D). The results revealed that the suppression of pro-inflammatory cytokines and activation of anti-inflammatory cytokines could be mediated through the polarization into M 2 macrophages, which would attribute to the healing mechanism of chronic wounds. , …”
Section: Resultsmentioning
confidence: 94%
“…The RT-PCR observation (Figure C) was consistent with the amounts of the aforementioned pro- and anti-inflammatory cytokines assessed by ELISA (Figure D). The results revealed that the suppression of pro-inflammatory cytokines and activation of anti-inflammatory cytokines could be mediated through the polarization into M 2 macrophages, which would attribute to the healing mechanism of chronic wounds. , …”
Section: Resultsmentioning
confidence: 94%
“…Moreover, the ceramic dressing showed bacterial retention properties and even demonstrated superior diagnostic properties compared to conventional wound swabs. The majority of chronic wounds do not progress beyond the inflammatory stage, which is characterized by poor perfusion, persistent inflammation, and bacterial burden [20][21][22]. These interactions lead to hard-to-heal wounds characterized by stagnated wound sizes.…”
Section: Discussionmentioning
confidence: 99%
“…As a biomaterial, collagen can interact with cells and the ECM of the recipient to promote cellular proliferation ( Parenteau-Bareil et al, 2010 ). Mammalian collagen scaffolds include Bio-ConneKt and HeliColl, among others ( Table 1 ) ( Sharma et al, 2023 ). Unfortunately, mammalian collagen has been associated with immunogenicity following implantation, with ethical controversy complicating its use ( Parenteau-Bareil et al, 2010 ).…”
Section: Current Approaches To Skin Engineeringmentioning
confidence: 99%